The Correlation Between Academic Stress and Psychological Well-Being Among High School Students in Indonesian Rural Areas - Farah Dineva R; Sri Novitayani; Asniar Asniar; Putri Mayasari (Rifa'Institute, 2026)
Introduction: Adolescents experience various pressures in meeting multiple demands in school life. As a result, adolescents can undergo academic stress. The emergence of academic stress affects psychological well-being. Objective: This study examines the correlation between academic stress and psychological well-being experienced by high school students in rural areas. Method: This study applied a correlational design and cross-sectional approach. The samples in this study were 82 students from two senior high schools in rural areas with the criteria of students aged 15-19 years participating in the Adolescent Reproductive Health Information and Counseling Center (PIK-R) program. Result and Discussion: The results showed the value of p = .003 (p < .05) with correlation coefficient (r) = - .319. Conclusions: It shows the existence of negative correlation between academic stress and psychological well-being. It is hoped that students can overcome problems related to their academics with a positive response and that all parties involved in the school can carry out programs that help students overcome stress